2010
DOI: 10.1038/onc.2010.291
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a pro-apoptotic function of RACK1 in human breast cancer

Abstract: We have read with great interest the recent article by Mamidipudi and Cartwright (2009), in which the authors showed that RACK1 induced apoptosis of human colon cells by inhibiting the expression of antiapoptotic pathways and Src activity, thus leading to death of colon cancer cells.We have recently conducted an analysis of RACK1 messenger RNA (mRNA) expression in 127 human breast cancer and 33 non-cancerous breast tissue specimens. The study was carried out using reverse transcriptase-polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…31 Interestingly, it has been recently described as a pro-apoptotic gene in human breast and colon cancer. 34 Finally, the chromosomal regions where these snoRNAs are located (see Table 1) have been previously reported by us to be transcriptionally active or specifically downregulated in HD patients. 18 Based on these findings, it could be suggested that snoRNAs expression in HD samples may have a role in the overall upregulation of the translational machinery.…”
Section: Discussionmentioning
confidence: 79%
“…31 Interestingly, it has been recently described as a pro-apoptotic gene in human breast and colon cancer. 34 Finally, the chromosomal regions where these snoRNAs are located (see Table 1) have been previously reported by us to be transcriptionally active or specifically downregulated in HD patients. 18 Based on these findings, it could be suggested that snoRNAs expression in HD samples may have a role in the overall upregulation of the translational machinery.…”
Section: Discussionmentioning
confidence: 79%
“…Specifically, RACK1 expression is being assessed as a prognostic indicator in breast cancer [203,204], where increased RACK1 expression is strongly related to advanced clinical stage [205]. In pulmonary adenocarcinomas, increased RACK1 expression is associated with pathological stage and tumor size and is also a potential diagnostic marker [206].…”
Section: Rack1 In Diseasementioning
confidence: 99%
“…In contrast, some reports suggest that RACK1 expression is reduced in breast cancer [207]. In addition, RACK1 may protect cells from apoptosis in breast cancer [204,208]. RACK1 is upregulated in hepatocellular carcinoma where it increases the translocation of A Disintegrin And Metalloprotease 12 (ADAM12) to the plasma membrane in response to PKC activation [209] and it is upregulated in metastatic melanoma, where it amplifies PKCα and PKCβ activity [210].…”
Section: Rack1 In Diseasementioning
confidence: 99%
“…RACK1 possesses the capacity for interaction with diverse proteins and plays important roles in a variety of physiological functions. The altered RACK1 expression has been identified in several kinds of human diseases, including brain developmental disorders, heart failure, muscle atrophy, breast cancer and pulmonary adenocarcinomas [16], [17], [18], and our previous research also indicates that RACK1 is frequently up-regulated in hepatocellular carcinoma and promotes its chemo-resistance and growth [19]. However, the role of RACK1 in liver fibrosis is little defined.…”
Section: Introductionmentioning
confidence: 96%